Ferramentas jornalísticas na educação: uma rádio online para jovens - Brites, Maria José (2021)
The relationship between journalism and education remains in a yet weakly explored camp, although journalism can embody a pedagogical tool, oriented to the practice of journalistic concepts and techniques. In this article, we explore a case-study of an online radio developed with youth communities, using participant observation, interviews and focus groups conducted in the scope of the project RadioActive Europe (2013-14). We argue that these young participants take similar roles in daily life and particularly in school to those used in contexts of radio participation. Learning through action, however, implies long lasting intervention processes so that the transposal of roles taken up in the project may be more perennial, dynamic and fluid in the personal life processes.